Pneumatocele triggered by continuous positive airway pressure after lung resection. (2020) - Fujibayashi, Yusuke; Ogawa, Hiroyuki; Nishio, Wataru; Nishikubo, Megumi; Nishioka, Yuki; Tane, Shinya; Kitamura, Yoshitaka; Yoshimura, Masahiro
Abstract: A pneumatocele is a cystic change of the lung that is caused by a check valve in the bronchiole due to infection, trauma and positive-pressure ventilation. We herein report a case of pneumatocele triggered by using of continuous positive airway pressure (CPAP) for sleep apnea syndrome (SAS) after pulmonary resection. A 69-year-old man underwent right upper lobectomy for lung cancer and developed interstitial pneumonia (IP) 10th postoperative day (POD). He was treated with steroid pulse therapy (solmedrol 500 mg × 3 days), and thereafter with oral steroid therapy (predonin 30mg/day). Well responded to the steroid therapy, IP was improved. However, he noticed bloody sputum 29th POD, and chest computed tomography showed a giant cystic lesion on the dorsal right lower lobe. We resected the cyst and the pathological findings revealed that the cystic lesion was pneumatocele, and CPAP was strongly suspected of triggering this disease.